2013
DOI: 10.1371/journal.pone.0083743
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Risk Factors Associated with Surgical Site Infections among Surgical Patients

Abstract: ImportanceSurgical site infection (SSI) complicates 2-5% of surgeries in the United States. Severity of SSI ranges from superficial skin infection to life-threatening conditions such as severe sepsis, and SSIs are responsible for increased morbidity, mortality, and economic burden associated with surgery. Staphylococcus aureus (S. aureus) is a commonly-isolated organism for SSI, and methicillin-resistant S. aureus SSI incidence is increasing globally.ObjectiveThe objective of this systematic review was to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
229
2
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(280 citation statements)
references
References 43 publications
(63 reference statements)
20
229
2
10
Order By: Relevance
“…increases in wound contamination class) were associated with decreased risk of S. aureus SSI. One the one hand, this is contrary to some evidence; 12,28 on the other hand, contaminated surgical procedures concern mostly abdominal surgery with enteric bacteria as most frequent causes of SSI. Moreover, we excluded polymicrobial SSI containing S.…”
mentioning
confidence: 78%
“…increases in wound contamination class) were associated with decreased risk of S. aureus SSI. One the one hand, this is contrary to some evidence; 12,28 on the other hand, contaminated surgical procedures concern mostly abdominal surgery with enteric bacteria as most frequent causes of SSI. Moreover, we excluded polymicrobial SSI containing S.…”
mentioning
confidence: 78%
“…Moreover, certain SSI predictors reported in the literature, such as age, S. aureus colonization, use of medical device, length of preoperative stay and surgery duration [35], were not captured in the NSQIP database and therefore, were not assessed in this analysis. Albeit, the study aim to create a user-friendly risk scoring tool may have been hindered by the inclusion of many variables.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors with continuous scales were dichotomized for statistical purposes. The BMI abnormality original classification included underweight (< 18.5), overweight (25)(26)(27)(28)(29)(30), class I obese (30)(31)(32)(33)(34)(35), class II obese (35)(36)(37)(38)(39)(40) and class III obese (> 40) groups as per pre-defined NSQIP BMI ranges. The altered classification classified BMI levels below 18.5 and above 25 as abnormal (under/overweight) and those between 18.5 and 25 as normal [27].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Some factors, such as patient age and gender are fixed but other potential variables, e.g., nutritional status, smoking, rational antibiotic use, compliance with asepsis-antisepsis techniques, technical conditions of the operating room, and intraoperative techniques, can be improved to provide positive surgical outcomes (1,16). A systematic review of 57 studies conducted in various countries showed that a high body mass index, severe wound class, diabetes, and a high NNIS risk index were associated with increased SSIs (17). The NNIS index is a classification developed by the CDC to identify risk of SSIs after surgery and compare the infection rates between surgical patients (18).…”
Section: Surgical Site Infection Risk Factorsmentioning
confidence: 99%